Cover Image, Volume 530, Issue 1. Issue 1 (29th December 2021) - Ding, Song‐Lin; Royall, Joshua J.; Lesnar, Phil; Facer, Benjamin A.C.; Smith, Kimberly A.; Wei, Yina; Brouner, Kristina; Dalley, Rachel A.; Dee, Nick; Dolbeare, Tim A.; Ebbert, Amanda; Glass, Ian A.; et al.
Abstract : The cover image represents three segmented atlas plates for the prenatal human brain at postconceptional week 15 (PCW 15). This article (Ding et al., 2022 ) presents two fully delineated cellular resolution anatomical reference atlases for the brains at PCW 15 and 21, respectively. The delineation of anatomical boundaries is based on a combined analysis of cytoarchitecture, acetylcholinesterase staining and spatial expression patterns of 43 genes (all from the same hemisphere). This article also provides detailed brain‐wide annotation of spatial localization of 37 and 5 genes respectively for the two brains. The combined approach makes many more prenatal brain structures identifiable and reveals several new findings on human brain development.